The DaNa projects: public communication of (nano)material safety data—from conspiracy theories to study quality - Kühnel, Dana; Krug, Harald F.; Steinbach, Christoph; Nau, Katja (Frontiers in Toxicology, 2024)
In this perspective, the authors give their view on the developments and experiences on communicating on (nano)materials safety. We would like to share our experiences with the scientific community in order to make them useful for future communication activities. We present the long-term work of the science communication projects DaNa, DaNa2.0 and DaNa4.0, running from 2009 to 2023. Starting in the early 2000s with the beginnings of nanotechnology research, communication on the safety of nanomaterials with the public was still very new and faced the projects with many challenges. Today, science communication is indispensable for the dissemination of scientific findings and a fact-based approach like the DaNa “Knowledge Base Materials” creates a trustworthy dialogue with the public. This long-term project series has made a significant contribution to communication on the safety of nanomaterials, perhaps even the largest among publicly funded project series worldwide.